Reading literacy and text processing skill development in an online learning environment - Habók, Anita; Magyar, Andrea (Iskolakultúra, 2020)
The online environment, compared to printed reading materials, increasingly determines upper elementary school students’ reading patterns. Compared to the lower grades the number of subjects increases from the upper grades, and in parallel the amount of texts related to the subjects also increases. While some of the texts are paper based, the other part should be read digitally. This new learning environment requires from students to practice their reading strategies online as well as to acquire new strategies. The skill development program presented in this study teaches reading comprehension and text processing strategies to upper elementary school students and enables them to practice these strategies. The content of the development program is subject-independent. Results indicated that the program can be applied in a classroom setting and can be solved through individual learning. The students' results called on our attention that the most difficult task was the cooperation during solving the tasks. The results indicated that this type of task should be more intensively practiced. Feedback from teachers will help improve the program in the future. Comments have shown that there is a need for more detailed, differentiated explanations and assistance to students. In relation to the different learning styles, besides demonstrations reading and explaining assignments would provide a more supportive environment. As our program aimed to create a student-friendly environment, which is also a motivation tool for the students, we plan to provide more detailed documentation of the learning outcomes.